2021
DOI: 10.13057/biodiv/d220237
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of polyprenol and dolichol in oil palm genotype (Elaeis guineensis) involving lipase activity

Abstract: Abstract. Habsyah TS, Basyuni M, Siregar LAM, Afandi D, Syahputra I. 2021. Distribution of polyprenol and dolichol in oil palm genotype (Elaeis guineensis) involving lipase activity. Biodiversitas 22: 830-837. The aim of this study was to determine the pattern of chemical compounds from the polyisoprenoid group in oil palm plants that were contributing to the lipase activity. The study was conducted in two locations. A sampling of leaves and fruit mesocarp from 90 progenies was conducted at PT. Socfin Indonesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Socfin Indonesia is classified as type II. The results of previous studies also indicated that leaf samples from sprouts and adult plants of Tenera (Afriyanto et al 2017), as well as leaf and mesocarp samples from 90 tested progeny (Habsyah et al 2021), were included in the polyisoprenoid type II distribution. This type of pattern becomes a chemotaxonomic marker for oil palm plants in agro-climatic conditions similar to the location of the research activity.…”
Section: Polyisoprenoid In Pisifera Parent Oil Palm At Pt Socfin Indonesia Dolok Masihul Estatementioning
confidence: 88%
“…Socfin Indonesia is classified as type II. The results of previous studies also indicated that leaf samples from sprouts and adult plants of Tenera (Afriyanto et al 2017), as well as leaf and mesocarp samples from 90 tested progeny (Habsyah et al 2021), were included in the polyisoprenoid type II distribution. This type of pattern becomes a chemotaxonomic marker for oil palm plants in agro-climatic conditions similar to the location of the research activity.…”
Section: Polyisoprenoid In Pisifera Parent Oil Palm At Pt Socfin Indonesia Dolok Masihul Estatementioning
confidence: 88%